Fatigability in spinal muscular atrophy: validity and reliability of endurance shuttle tests - Bart Bartels; Janke F. de Groot; Laura E. Habets; Camiel A. Wijngaarde; Wendy Vink; Marloes Stam; Fay-Lynn Asselman; Ruben P. A. van Eijk; W. Ludo van der Pol (Orphanet Journal of Rare Diseases, 2020)
Abstract Background To determine construct validity and test-retest reliability of Endurance Shuttle Tests as outcome measures for fatigability of remaining motor functions in children and adults with Spinal Muscular Atrophy (SMA) across the severity spectrum. Results We assessed the Endurance Shuttle - Nine Hole Peg Test (ESNHPT), − Box and Block Test (ESBBT) and – Walk Test (ESWT) in 61 patients with SMA types 2–4, 25 healthy controls (HC) and 15 disease controls (DC). Convergent validity, discriminative validity and test-retest reliability were investigated. Additionally, we compiled the Endurance Shuttle Combined Score (ESTCS) by selecting the most relevant endurance test of each individual. 54, 70 and 73% of patients with SMA demonstrated increased fatigability on the ESNHPT, ESBBT and the ESWT. Endurance response in SMA was characterized by a decrease in muscle strength, an increase in muscle fatigue and an increase in motor adaptions, thereby confirming convergent validity. Patients with SMA showed increased drop-out rates and a shorter endurance time compared to HC and DC demonstrating good discriminative validity. Test-retest reliability was moderate to excellent (ICC’s ranging from .78 to .91) with a trend towards better performance on retest. The ESTCS increased sample size and drop-out rate up to 100 and 85%. Conclusions Fatigability is an important additional dimension of physical impairments across the severity spectrum in children and adults with SMA. The EST’s are reliable and valid to document fatigability of walking, proximal- and distal arm function in SMA and thus are promising outcome measures for use in clinical trials.